2008
DOI: 10.1074/mcp.m700459-mcp200
|View full text |Cite
|
Sign up to set email alerts
|

Increased α-Defensins as a Blood Marker for Schizophrenia Susceptibility

Abstract: Schizophrenia is a severe psychotic illness affecting 1% of the general population. There are no consistent pathological features, and the disorder is defined by a complex symptomatology, which overlaps with other psychiatric illnesses. Diagnosis is based on a clinical interview, relying on the patient meeting criteria according to diagnosis manuals, including Diagnostic and Statistical Manual of Mental Disorders, 4th Ed. and International Statistical Classification of Diseases, 10th Revision. Because of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 32 publications
2
44
0
1
Order By: Relevance
“…In psychiatry, such studies have involved the use of whole blood [129131] , lymphocytes [132] or PBMC samples [133135] to identify potential biomarkers for Sz. Other studies examined proteomics information in RBC [109] , T cells [136] , and serum [61,109,137,138] in attempts to answer the same question. This approach has typically led to a large set of mRNAs or proteins being proposed as possible biomarkers in Sz but most findings await replication.…”
Section: The Human Transcriptome and Human Proteome Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In psychiatry, such studies have involved the use of whole blood [129131] , lymphocytes [132] or PBMC samples [133135] to identify potential biomarkers for Sz. Other studies examined proteomics information in RBC [109] , T cells [136] , and serum [61,109,137,138] in attempts to answer the same question. This approach has typically led to a large set of mRNAs or proteins being proposed as possible biomarkers in Sz but most findings await replication.…”
Section: The Human Transcriptome and Human Proteome Studiesmentioning
confidence: 99%
“…Taken together, there is only downregulation of intercellular adhesion molecule in people with Sz that were replicated in at least two microarray studies [138,140] . Other studies have identified markers that may be of use in identifying people who are at risk of developing the disorder, such as the up-regulation of DEFA in T cells and plasma from people with Sz, and both their affected or unaffected monozygotic twin [136] . Of interest is the downregulation of apolipoprotein A1 identified in both red blood cells of people with Sz and serum of people with Sz who were drugnaive [109] .…”
Section: The Human Transcriptome and Human Proteome Studiesmentioning
confidence: 99%
“…Furthermore, the results of a twin-based study suggest that antimicrobial peptides (α-defensins) might be early markers for the risk of developing schizophrenic symptoms later in life [37]. Another study found that the acute-phase proteins C3 and C4 as well as ceruloplasmin, which interestingly also possess antimicrobial properties, correlate with negative symptoms in acute paranoid schizophrenia [38].…”
Section: Immunological Parameters As Possible Markersmentioning
confidence: 99%
“…We have shown that human a-defensins can induce platelet activation [21]. An increased level of a-defensins was shown to be a blood marker for schizophrenia susceptibility [22]. These peptides have also been described as early markers for the development of colorectal adenomas and carcinomas, and it has been suggested that they might contribute to tumor growth [23].…”
Section: Discussionmentioning
confidence: 99%